KELOMPOK SIMPAN PINJAM PEREMPUAN DI DESA BATU BELANAK KECAMATAN SUAK MIDAI KABUPATEN NATUNA - Bambang Suhito; Nanik Rahmawati; Siti Arieta (JURNAL SOSIO-KOMUNIKA, 2023)
The Women's Savings and Loans activity is an activity that provides loans for business capital for women in poor households. However, many members did not use these funds for business or in the use of funds that were not in accordance with the proposals made, so that made researchers interested in examining the problems that exist in women's savings and loan activities in Batu Belanak Village, Suak Midai District, Natuna Regency. The purpose of this study was to determine the behavior of the use of funds by the Women's Savings and Loans group in Batu Belanak Village, Suak Midai District, Natuna Regency. This study uses a qualitative method with a descriptive approach. The technique in determining the informants used purposive sampling technique with a total of 11 informants obtained from the main informant, namely members of the SPP group. This research uses the theory of Rational Choice by James S Coleman The findings from this study are that the behavior of utilizing funds for women's savings and loan activities in Batu Belanak Village is 1). The Women's Savings and Loans Fund which is supposed to be for business capital but is used for consumptive things, to help increase the husband's business capital and there is also to help with the facilities and needs of the husband's work. 2) There are some members who also use women's savings and loan funds to be used for business 3). Funds used by men using a woman's name or using a woman's name. In conclusion, women's savings and loan activities in Batu Belanak Village are still ineffective because there are still many community members who use the funds not in accordance with the contents of the proposal they made or are not used properly. The Management Unit is expected to be more selective and it is hoped that there will be monitoring and supervision in the field so that the program is right on target considerations.